Association of Positive Family History and Clinicopathological Features in Breast Cancer in Young Indian Females – A Pilot Study - Jaishree Goyal; Ajay Yadav; Hemant Malhotra (Journal of Radiation and Cancer Research)
Introduction: Breast cancer is the most common cancer in Indian females, accounting for 31.8% of all cancers. Young women with breast cancer are those under 40 years of age. These patients have higher chances of positive family history and genetic susceptibility. Approximately 5%–10% of cases of breast cancer are associated with a family history. In this study, we planned to identify a relationship between family history and the clinical, pathological, and genetic characteristics of breast cancer in young women. Methods: Retrospectively, data from patients aged < 40 years with breast cancer, were collected from 2019 to 2022. Detailed information about the family history of the patients including the degree and number of relatives affected and the types of cancer was recorded. The tumors were characterized based on the pathological grade, estrogen receptor, progesterone receptor, human epidermal growth factor receptor 2 status, and BRCA variant genetic analysis. Results: Of 125 females with young breast cancer, 24 patients (19%) had a first- or second-degree relative with a history of cancer at the time of breast cancer diagnosis. Four (16%) of these positive cases had BRCA mutation detected. Bilateral breast cancer was detected in 12% of women with positive family history. Conclusion: Clinicians are urged to use detailed family histories for young women with breast cancer for early screening and education of the first- and second-degree relatives of these patients to detect the hidden cases.